A case study of high sea salt aerosol (SSA) concentrations as a hazard to aviation. (11th November 2015) - Tighe, Tony
ABSTRACT: On the night of 2 January 2014, an aircraft on approach to Cork airport was required to abort a landing attempt due to sea salt aerosol (SSA) accretion on the windscreen. The salt reduced forward‐facing visibility to dangerously low levels and prohibited a safe approach by the aircraft. A landing was eventually effected on the 3 rd attempt after a light rain shower cleared enough of the contaminant to allow the pilot to view the runway lights and markings. This was the first time such an incident was recorded by Ireland's Air Accident Investigation Unit. This paper elaborates the meteorological conditions present at the time the SSA became a visibility hazard. The atmospheric boundary layer was thermodynamically unstable and had a relatively dry airmass and the surface and upper level winds were high. SSA formation mechanisms are described in terms of the relationship between SSA concentration enhancement and meteorological variables. A brief comparison between the meteorological conditions surrounding this and another notable event documented by the US naval service is made. The potential for SSA to be a significant hazard to aviation and the recommendations for further research are considered.